Development of polymorphic microsatellite markers for a rare dragonfly, Cordulegaster sarracenia (Odonata: Cordulegastridae), with notes on population structure and genetic diversity. Issue 3 (3rd July 2018) - Abbott, Kendra K.; Abbott, John C.; Lozier, Jeffrey D.; Beasley, Rochelle R; Lance, Stacey L.
Abstract : We isolated and characterized a total of 13 microsatellite loci from Cordulegaster sarracenia (Odonata: Cordulegastridae) . Loci were screened in 24 individuals from Louisiana and Texas. Within C. sarracenia, the number of alleles per locus ranged from 0 to 5, and observed and expected heterozygosities ranged from 0.000 to 0.556 and 0.000 to 0.613, respectively. Overall differentiation among study populations was very high ( F ST  = 0.423), suggesting significant geographic population structure with low diversity within populations. Twelve of the 13 primers amplified in C. sayi, C. diastatops, C. maculata, and C. obliqua and polymorphism levels are reported. These new genetic markers will provide tools for addressing a number of population genetic and demographic questions relating to conservation of this rare dragonfly species.